CDA for Symbolic Violence Analysis: Constructing Theories of Symbolic Violence and Critical Discourse Analysis in the Study of Educational Textbook - Hakim, Mohammad Andi; Wawan Gunawan; Budi Hermawan (Universitas Nahdlatul Ulama Blitar, 2024)
This research formulates a new construction of symbolic violence analysis in educational textbooks. Analysis of symbolic violence through critical sociological theory is still limited to generalizing linguistic evidence. The integration of two important theories, cultural reproduction through symbolic violence by Pierre Bourideu and Critical Discourse Analysis by Teun A van Dijk, became the main study formulated. The study focused on reconstructing the concept of CDA for Symbolic Violence Analysis as a combination of these two theories in the study of educational textbooks. A qualitative approach with a library research as the research method was carried out. The reconceptualization of these two theories is able to present an analytical model to dismantle the ideological structures hiding behind educational texts. Symbolic violence that occurs through the process of cultural reproduction and gives rise to forced doxa can be dismantled through analysis of habitus, capital and arena which is enhanced by textual analysis, social cognition and social context.